Non-canonical amino acids as a tool for the thermal stabilization of enzymes - Lugtenburg, Tim; Gran-Scheuch, Alejandro; Drienovská, Ivana (Protein engineering, design and selection, 2023)
Abstract Biocatalysis has become a powerful alternative for green chemistry. Expanding the range of amino acids used in protein biosynthesis can improve industrially appealing properties such as enantioselectivity, activity and stability. This review will specifically delve into the thermal stability improvements that non-canonical amino acids (ncAAs) can confer to enzymes. Methods to achieve this end, such as the use of halogenated ncAAs, selective immobilization and rational design, will be discussed. Additionally, specific enzyme design considerations using ncAAs are discussed along with the benefits and limitations of the various approaches available to enhance the thermal stability of enzymes. Graphical abstract